The effect of a training impact of a training mesozycle of annual cycle of preparation on the physical preparedness and functional condition of the rowers of 16-17 years women - Verlin, S. V.; Abramova, T. F.; Golovachev, A. I.; Nikitina, T. M.; Buchina, E. V.; Polfuntikova, A. V.; Mingazova, D. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
The effect of training loads of the beginning of the preparation period of the training period on the level of physical fitness and functional state of female athletes specializing in academic rowing has been studied. According to the standardized program, at the beginning and after the completion of the 30-day inducing mesocycle, 11 athletes aged 16-17 years were examined, with work experience of 3-4 years, with qualification from grade I to km. The program of comprehensive surveys included the conduct of test procedures aimed at assessing the indicators of physical performance, morphological status, functional status of energy supply systems, and leading physical qualities. Modern research methods were used: anthropometry, caliperometry, ergometry, gasometry, pulsometry, tonometry, blood biochemistry, isokinetic dynamometry of leg strength, tensometry. It is shown that the construction of the training process with the predominant use of training loads of a cyclical nature in combination with loads aimed at the development of maximum strength at the beginning of the preparatory period in the 30-day "pull-in" mesocycle in highly skilled rowers 16-17 years old, have a positive impact on the formation of the morphological status (primarily through reducing excess body fat, mainly localized on the abdomen and thigh), increasing the level of physical performance by increasing the power and economization potential of the oxidative and lactic acid energy systems, the growth of functional economization, manifested in the activity of the cardiovascular system and the elimination of physical qualities, evaluated in dynamic and static modes of muscular activity to the level of development of maximum strength, speed and strength endurance (by segments and complete leg work), providing a smooth transition to specialized loads (more high intensity)